Are diagnostic criteria for acute malnutrition affected by hydration status in hospitalized children? A repeated measures study - Mwangome, M; Fegan, G; Prentice, A; Berkley, J (2011)
Introduction. Dehydration and malnutrition commonly occur together among ill children in developing countries. Dehydration (change in total body water) is known to alter weight. Although muscle tissue has high water content, it is not known whether mid-upper arm circumference (MUAC) may be altered by changes in tissue hydration. We aimed to determine whether rehydration alters MUAC, MUAC Z score (MUACz), weight-for-length Z-score (WFLz) and classification of nutritional status among hospitalised Kenyan children admitted with signs of dehydration. Study procedure. We enrolled children aged from 3 months to 5 years admitted to a rural Kenyan district hospital with clinical signs compatible with dehydration, and without kwashiorkor. Anthropometric measurements were taken at admission and repeated after 48 hours of treatment, which included rehydration by WHO protocols. Changes in weight observed during this period were considered to be due to changes in hydration status. Results: Among 325 children (median age 11 months) the median weight gain (rehydration) after 48 hours was 0.21 kg, (an increase of 2.9% of admission body weight). Each 1% change in weight was associated with a 0.40 mm (95% CI: 0.30 to 0.44 mm, p < 0.001) change in MUAC, 0.035z (95% CI: 0.027 to 0.043z, P < 0.001) change in MUACz score and 0.115z (95% CI: 0.114 to 0.116 z, p < 0.001) change in WFLz. Among children aged 6 months or more with signs of dehydration at admission who were classified as having severe acute malnutrition (SAM) at admission by WFLz <-3 or MUAC <115 mm, 21% and 19% of children respectively were above these cut offs after 48 hours. Conclusion: MUAC is less affected by dehydration than WFLz and is therefore more suitable for nutritional assessment of ill children. However, both WFLz and MUAC misclassify SAM among dehydrated children. Nutritional status should be re-evaluated following rehydration, and management adjusted accordingly. © 2011 Mwangome et al; licensee BioMed Central Ltd.